DIVERSIDADE GENÉTICA EM MILHO CRIOULO ATRAVÉS DOS MARCADORES MOLECULARES RAPD, MICROSSATÉLITE E AFLP - Molin, Dayane (2012)
The wide variability in corn is due to the numerous landraces, important genotypes for breeding programs, because they constitute a source of genetic variability in the exploration of new genes of economic interest. The objectives were to analyze the genetic diversity between landraces from Rio Grande do Sul and Paraná through the analysis of polymorphism generated by RAPD, microsatellite (SSR) and AFLP markers; cluster these genotypes through estimates of genetic similarity and establish possible relationships between genetic similarity and the sampling sites of the landraces. PCR reactions for each marker were optimized through specific protocols being used: 30 RAPD primers, 47 SSR primers pairs and 25 combinations of primers for the EcoRI + MseI for the AFLP marker. The amplified fragments (RAPD and SSR) were visualized in agarose gel at 2 and 3 %, respectively, through horizontal electrophoresis run for approximately 4 h at 80 V. The AFLP amplification products were resolved on a polyacrylamide gel (6 %) submitted to a vertical electrophoresis run for 3 h 30 min at 80 W (1500 V). Genotyping of the varieties of corn with the RAPD marker amplified 409 fragments with a polymorphism average rate of 81.9 %. The SSR generated 134 fragments with 78.3 % of polymorphism. On the other hand, the AFLP amplified 1889 fragments with a polymorphism average rate of only 40.3 %. The polymorphic fragments were submitted to analysis of genetic similarity using the Jaccard coefficient and UPGMA clustering method individually and jointly for all markers. The coefficient mean of similarity was 57 % for RAPD, 56 % for SSR, 74 % for the AFLP and 69 % for the joint analysis. The dendrograms obtained from RAPD and SSR showed 8 different groups, while the dendrogram obtained from AFLP and the joint analysis formed six and seven groups, respectively. In general, the correlations between the similarity matrices were low, but between the AFLP and combined analysis was 96 %. Results revealed a wide genetic variability among landraces. The RAPD and SSR had the highest average rates of polymorphism and AFLP showed the highest rates of genetic similarity among landraces. In general, the markers used were effective tools for sampling the genetic diversity and cluster varieties according to the sampling sites, although they have differential capacity to reveal polymorphism as well as to cluster the landraces.